2001
DOI: 10.1034/j.1600-0846.2001.007001065.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency ultrasound imaging of the skin during normal and hypertensive pregnancies

Abstract: The data used to compare the groups indicates that if the abdominal skin of the patient does not get thinner as the pregnancy progresses there is an indication that the patient may be hypertensive. The fractal data comparing the groups indicates the following when comparing a patient's fractal signature with the non-pregnant control data: If the abdominal fractal for a pregnant woman is similar to the control group, there is an indication that the patient is hypertensive. It is difficult to predict hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Given the importance of tissue oedema, there have been surprisingly few published studies that examine the reduction of oedema during NPWT, although Kamaloz et al showed improved blood flow following NPWT versus controls in a study of bilateral burn wounds to the hands using indocyanine green video angiography which was ascribed to reduction of tissue oedema (11). High frequency diagnostic ultrasound (HFDU) is a noninvasive method, which allows the clinician to get a high-resolution image of the wound and surrounding tissue (12)(13)(14)(15). This simple procedure can often be used without removing the dressing.…”
Section: Key Messagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of tissue oedema, there have been surprisingly few published studies that examine the reduction of oedema during NPWT, although Kamaloz et al showed improved blood flow following NPWT versus controls in a study of bilateral burn wounds to the hands using indocyanine green video angiography which was ascribed to reduction of tissue oedema (11). High frequency diagnostic ultrasound (HFDU) is a noninvasive method, which allows the clinician to get a high-resolution image of the wound and surrounding tissue (12)(13)(14)(15). This simple procedure can often be used without removing the dressing.…”
Section: Key Messagesmentioning
confidence: 99%
“…The scanner used in this study was the Episcan (Longport International Ltd, Reading, UK). The device was operated at a frequency of 20 MHz as previously described (12)(13)(14)(15)(16). This frequency gives an axial resolution of 60 μm.…”
Section: Ultrasound Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous ultrasonography has been extensively used in human dermatology to study normal skin echogenicity, thickness and hydration status, as well as the echogenicity patterns of various pathological conditions, including cutaneous or subcutaneous neoplasms, cysts, inflammatory lesions, postradiation reactions, scleroderma, oedema, wounds and the presence of foreign bodies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Depending on the tissue-penetration properties of the ultrasound beam, cutaneous ultrasonography has been classified into intermediate and high-frequency ultrasonography (20 MHz or higher). 15 Only a few studies on the ultrasonographic examination of canine skin have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous ultrasonography has been extensively used in human dermatology to study normal skin echogenicity, thickness and hydration status, as well as various pathologic conditions, including cutaneous or subcutaneous neoplasms, cysts, inflammatory lesions, post-radiation reactions, scleroderma, edema, wounds, and presence of foreign bodies (Alexander and Miller 1979;Miyauchi and Miki 1983;Fornage and Deshayes 1986;Fornage et al 1993;Fornage 1993;Gniadecka 1996;Gniadecka and Quistorff 1996;Warszawski et al 1997;Milner et al 1997;Cammarota et al 1998;Foster et al 2000;Eisenbeiss et al 2001;Mirpuri et al 2001;Dyson et al 2003;Scope and Halpern 2003;Kong et al 2008). Contrary to the situation in human medicine, in veterinary medicine only few studies on cutaneous ultrasonography of the canine skin are available (Diana et al 2004;Mantis et al 2005;Mantis et al 2007;Diana et al 2008;Zanna et al 2012;Mantis et al 2014).…”
Section: The Historymentioning
confidence: 99%